FEATURES OF INCLUSIVE EDUCATIONAL ENVIRONMENT FORMATION FOR PEOPLE WITH SPECIAL NEEDS - Nataliіa Rodina (Неперервна професійна освіта: теорія та практика, 2021)
The article highlights the problem of forming an inclusive educational environment for people with special problems, analyzes the conceptual framework and basic regulations on the development of inclusive education in Ukraine, describes and expands the essence and content of such concepts as «Environment», «educational environment», «inclusive educational environment», «people with special needs»; characterises general didactic principles of inclusive education, determines the main priorities and components of inclusive educational environment that will be formed on the principles of accessibility, humanity and efficiency; establishes its main features, highlights the main areas of psychological assistance to people with psychophysical development problems, their socialization in society. The multidimensionality of definitions and definitions in the process of characterization of the basic components of the educational environment is characterized. Various opinions and approaches to understanding the essence of the concept of «educational environment» are considered. The own understanding of inclusive educational environment as a type of educational environment, which provides all subjects of the educational process with equal opportunities for effective self-development, provides a solution to the problem of educating people with special needs by adapting educational space to the needs of each person, variability, favourable psychological microclimate, re-planning of educational facilities so that they meet the needs of all participants in the educational process without exception and ensure the full participation of people in the educational process. The characteristics of inclusive educational environment as a system of values to the personal development of people with special educational needs, the set of resources (means, internal and external conditions) of their lives in educational institutions and the focus on individual educational strategies.